Enhancing Athletes Anti-doping Education Through Mobile Applications: A Review of Current Strategies and Emerging Technologies - Saragih, Zaini Kadhafi; ., Junaidi; ., Samsudin (KnE Social Sciences, 2024)
Anti-doping education is crucial for ensuring fairness and integrity in sports. The WADA implemented the ADeL certification program to provide comprehensive antidoping education for athletes. Mobile applications offer a user-friendly and accessible medium for delivering anti-doping education. ADOs employ various strategies to educate athletes, including developing educational materials, conducting workshops, partnering with schools and sports organizations, using technology, targeting high-risk groups, promoting a clean sports culture, and providing support services. Research has shown that anti-doping education is effective in increasing athletes’ knowledge and awareness of doping, and in decreasing doping intentions among adolescent athletes. ADOs are exploring new approaches to anti-doping education such as the use of virtual reality and artificial intelligence. Mobile applications are powerful tools for anti-doping education because they can reach a wider audience, provide personalized learning experiences, and foster clean sports culture. Keywords: anti-doping education, athletes, mobile applications, anti-doping education and learning (ADeL) certification program, WADA, clean sports